Localization of Impact Force Occurring on Elastic Plates by Using a Particle Swarm Algorithm. (2016) - El-Bakari, Abdelali; Khamlichi, Abdellatif; Jacquelin, Eric
Abstract: Identifying the characteristics of the force generated by impact can be used to better determine the residual health of structures that are susceptible to undergo impacts. This can enable to reduce hugely the required experimental effort that may be needed in order to assess completely the actual state of the structure as it could be damaged by the action of forces generated during these accidental events. This paper presents the application of a Particle Swarm Optimization technique to solve the localization problem associated to an impact that cannot be reduced to a point and occurring on homogeneous and isotropic elastic plates. This was performed through minimizing the root mean square error between the measured and the calculated responses. The problem was recognized to have the general form of parametric identification. The impacting force was assumed to result from uniformly distributed pressure acting over a rectangular patch. The Particle Swarm Optimization model has demonstrated high computational efficiency in finding the impact patch location. A parametric study was conducted finally to analyze sensitivity of the procedure to the number of sensors.